MRI based morphological examination of the placenta. (November 2021) - Arthuis, Chloé; Millischer, Anne-Elodie; Bussières, Laurence; Mahallati, Houman; Henry, Charline; Ville, Yves; Salomon, Laurent Julien; Grévent, David
Abstract: Ultrasound is widely used as the initial diagnostic imaging modality during pregnancy with both high spatial and temporal resolution. Although MRI in pregnancy has long focused on the fetus, its use in placental imaging has greatly increased over recent years. In addition to the possibilities of evaluating function, MRI with a wide field of view and high contrast resolution allows characterization of placental anatomy, particularly in situations that are difficult to specify with ultrasound, especially for suspected placenta accreta. MRI also appears to be a particularly useful examination for the anatomical evaluation of the placenta independent of maternal body habitus or fetal position. Indeed, surprisingly little attention is paid to the placenta in MRI when the indication for the examination is fetal. Thus, some aspects of the placenta seem to us to be important to be recognized by the radiologist and to be described on the MRI report. In this review, we will describe MRI sequences used for, and common features seen in, imaging of i) the normal placenta, ii) abnormal aspects of the placenta that should be identified on MRI performed for fetal reason, and iii) placental anomalies for which placental MRI may be indicated. Highlights: It is important to consider looking at the placenta during an MRI examination. It is important to know how to recognize particular aspects of the placenta because its impact the obstetrical management. The major elements not to be missed during prenatal MRI are the low lying placenta and the well-described signs of PAS.